Examining the Relationship between Employee Resistance to Changes in Job Conditions and Wider Organisational Change: Evidence from Ireland - Hugh Cronin; Seamus McGuinness (Institute for the Study of Labor (IZA), 2014)
This paper uses a linked employer-employee dataset, the National Employment Survey, to examine the determinants of organisational change and employee resistance to change and, specifically, to examine the influence of employee inflexibility on the implementation of firm-level policies aimed at increasing competitiveness and workforce flexibility. Key finding arising from the research is that while workforce resistance to job-related change often forces firms to seek alternative means of achieving labour flexibility, there appears little that firms can do to prevent such resistance occurring. The presence of HRM staff, consultation procedures, wage bargaining mechanisms, bullying and equality polices etc were found to have little impact on the incidence of workforce resistance to changes in job conditions.
Keywords: J31; J51; J53; 330; workforce resistance; organisational change; linked employer-employee data